Associations between number of siblings, birth order, eating rate and adiposity in children and adults. Issue 3 (12th January 2021) - Potter, Christina; Gibson, E. Leigh; Ferriday, Danielle; Griggs, Rebecca L.; Coxon, Christle; Crossman, Margot; Norbury, Ray; Rogers, Peter J.; Brunstrom, Jeffrey M.
Summary: Eating quickly is associated with eating larger amounts at mealtimes and faster eaters tend to have a higher BMI. Evidence suggests that sibling structure influences the development of childhood eating behaviours. We hypothesized that number of siblings and birth order might play a role in the development of eating rate. In two UK studies, children in Bristol ( n = 132; Study 1) and adults and children in London (adults n = 552, children n = 256; Study 2) reported their eating rate, number of siblings, and birth order. A BMI measurement was obtained and in Study 2 waist circumference was recorded. Ordered logistic regression was used to examine effects of sibling structure on eating rate and linear regression assessed effects of eating rate on BMI. Faster eating was associated with higher BMI and a larger waist, in children and adults (ps < .01). In Study 1, first‐born children were twice as likely to eat faster compared to children who were not first‐born ( P < .04). In Study 2, only‐child adults reported eating slower than adults who were not first‐born ( P < .003). Additionally, higher number of siblings was associated with faster eating rate in children from Bristol ( P < .05), but not in children from London. London adults without siblings ate slower than those with two or more ( P = .01), but having one sibling was associated with eating faster than having two or more ( P = .01). These findings reveal how birth order and number of siblings might influence eating rate. Exploring these relationships through direct observation would be beneficial in future studies.